2000
DOI: 10.1002/14651858.cd000988
|View full text |Cite
|
Sign up to set email alerts
|

Buflomedil for intermittent claudication

Abstract: BackgroundIntermittent claudication (IC) is pain caused by chronic occlusive arterial disease, that develops in a limb during exercise and is relieved with rest. Buflomedil is a vasoactive agent used to treat peripheral vascular disease. However, its clinical efficacy for IC has not yet been critically examined. This is an update of a Cochrane review first published in 2000, and previously updated in 2007 and 2008. ObjectivesTo evaluate the available evidence on the efficacy of buflomedil for IC. Search method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…The incidence of buflomedil poisoning and the severity of the cases remained stable between 2006 and 2008 [40]. In the meantime, a review from the Cochrane collaboration concluded that buflomedil has little benefit in patients with intermittent claudication [41].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of buflomedil poisoning and the severity of the cases remained stable between 2006 and 2008 [40]. In the meantime, a review from the Cochrane collaboration concluded that buflomedil has little benefit in patients with intermittent claudication [41].…”
Section: Discussionmentioning
confidence: 99%
“…Nach einem Cochrane-Review gibt es nur wenig Evidenz für eine therapeutische Wirksamkeit von Buflomedil bei Claudicatio intermittens (De Backer et al 2001). Nach einem Cochrane-Review gibt es nur wenig Evidenz für eine therapeutische Wirksamkeit von Buflomedil bei Claudicatio intermittens (De Backer et al 2001).…”
Section: Buflomedilunclassified